Patient characteristics associated with easy and poor tolerance of moderate sedation during endoscopy. Issue 3 (14th May 2019) - Curtin, Bryan F.; Strongin, Anna; Surana, Pallavi; Farooqi, Rehan; Haydek, Christopher; Heller, Theo; Kumar, Sheila; Koh, Christopher
Summary: Background: Appropriate levels of sedation are paramount for optimising patient comfort, safety and technical success during endoscopy. The goal of this cross‐sectional study was to identify factors associated with patient tolerance of moderate sedation during esophagogastroduodenoscopy (EGD) and colonoscopy. Methods: Endoscopic procedures performed under moderate sedation from 2004 to 2018 at the NIH were reviewed. Patients were categorised as "poorly tolerated, " based on the assessment of the performing endoscopist, or "easily sedated, " based on low levels of sedation (fentanyl 50 mcg and midazolam ≤2 mg). Epidemiologic and anthropometric data, type of procedure, inpatient/outpatient status and benzodiazepine/opiate use were analysed and compared between the two sedation groups. Results: Over a 14‐year period, 7590 endoscopies were assessed (4442 EGDs and 3148 Colonoscopies). A total of 359 patients met criteria for inclusion; 242 were categorised as "easy to sedate" (162 EGDs and 80 colonoscopies) and 118 as "difficult to sedate" (62 EGDs and 56 colonoscopies). For EGDs, younger age, African American race and nonscreening indication were associated with difficult sedation. For colonoscopies, young age, low/normal weight and White/African American race were all associated with more difficult sedation. Conclusions: Patients who are female, young and have a lower BMI are more likely to poorly tolerate procedures with moderate sedation. Persons of Hispanic/Asian descent appear to tolerate moderate sedation significantly better than other races. Clinicians should be aware of these factors when determining the type of sedation that will optimise success of endoscopy.